2019
DOI: 10.1016/j.jad.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between alexithymia and suicide ideation and behaviour

Abstract: Highlights Alexithymia is more closely related to suicide ideation than to suicide behaviour. The subcomponents of difficulty identifying and describing feelings are more closely related to suicide ideation and behaviour than the subcomponent of externally oriented thinking. The relationship between alexithymia and suicide ideation appears robust when controlling for confounding variables, though the relationship between suicide behaviour and alexithymia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 91 publications
6
40
0
3
Order By: Relevance
“…In addition, it should be noted that our review focused only on a limited set of variables, while other individual/clinical factors, relatively easy to assess in clinical practice, may play a role, such as childhood maltreatment/adversities, [124][125][126] inflammatory markers, 127,128 other symptom profiles or individual features. Among the latter, alexithymia, reflecting difficulty with identifying and expressing emotions, seems to be associated with higher severity of depression, increased suicide risk, and pro-inflammatory imbalance; [129][130][131][132][133] thus its potential contribute to selection of specific antidepressant class/compound may be worth investigating. Finally, we did not include combined pharmacotherapies, augmentation strategies, or non-pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it should be noted that our review focused only on a limited set of variables, while other individual/clinical factors, relatively easy to assess in clinical practice, may play a role, such as childhood maltreatment/adversities, [124][125][126] inflammatory markers, 127,128 other symptom profiles or individual features. Among the latter, alexithymia, reflecting difficulty with identifying and expressing emotions, seems to be associated with higher severity of depression, increased suicide risk, and pro-inflammatory imbalance; [129][130][131][132][133] thus its potential contribute to selection of specific antidepressant class/compound may be worth investigating. Finally, we did not include combined pharmacotherapies, augmentation strategies, or non-pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants reported memories of being exposed to prolonged and uncontrollable invalidating family environments, similar to those described by Linehan (Linehan, 1993), in which parents punish, trivialise and disregard their children's emotional and personal difficulties. Studies have demonstrated that such negative perceptions of early experiences are associated with the development of a series of mental health issues including alexithymic tendencies (difficulties in identifing and describing emotions in the self (Kench & Irwin, 2000), which has also been shown to be associated with suicidal thoughts (Hemming et al, 2019)), borderline personality symptoms (Schuppert, Albers, Minderaa, Emmelkamp, & Nauta, 2015), and self-harm (Baetens et al, 2015;Burešová, Bartošová, & Čerňák, 2015).…”
Section: Challenging Relationships As Catalysts For Stbmentioning
confidence: 99%
“…It has been suggested that emotion regulation difficulties may play a role in both suicide (Rajappa et al, 2012;Zlotnick et al, 1997) and violence (Davidson et al, 2000;Roberton et al, 2012). Specifically, one form of emotion dysregulation which has been hypothesised as relating to both suicide and violence is alexithymia Hemming, Taylor et al, 2019). Alexithymia can be defined as an inability to identify or express emotions and consists of three main factors; difficulty identifying feelings, difficulty describing feelings and a focus on externally oriented thinking patterns (Sifneos, 1973).…”
Section: Introductionmentioning
confidence: 99%